The Conceptual Relationship of Law of Attraction with Islamic Spirituality: A Study of the Quranic Law of Attraction - Rafa Arub; M. Indra Saputra; Uswatun Hasanah; Baharudin Baharudin; Agus Susanti (Universitas Syiah Kuala, 2025)
This study examines the concept of Law of Attraction (LoA) and its relationship with Islamic spirituality, focusing on the comparison of the basic principles of LoA and Islamic teachings in building a positive mindset, affirmation, visualization, and confidence in the desired results. This study uses a qualitative method with a descriptive-analytical approach through a literature review of the concept of LoA explained in the book The Secret by Rhonda Byrne and Quranic Law of Attraction by Rusdin S. Rauf. The analysis was carried out by comparing the principles of LoA with values in Islamic teachings, such as prayer, tawakkal, and gratitude. The results show that LoA and Islam have similarities in emphasizing the importance of positive thinking, focusing on goals, and affirmation and visualization as tools to strengthen beliefs. However, there are fundamental differences in the sources of power that are believed; LoA relies on the energy of the universe, while Islam affirms that everything happens by Allah's will. Therefore, the application of LoA for a Muslim must remain within the framework of the Islamic faith, without replacing belief in Allah with belief in the power of the mind alone. The principles of LoA can be applied in the life of a Muslim as long as it remains in harmony with the teachings of Islam, namely by understanding that human efforts must be accompanied by prayer and tawakkal to Allah. This study is expected to be a reference for the development of a more balanced understanding of LoA from an Islamic perspective. Further research is suggested to explore the application of this concept in practical aspects of life as well as how LoA can contribute to improving the motivation and spiritual well-being of Muslims.